Analysis of Stock Price Volatility in the Jakarta Islamic Index (JII) During the Implementation of the Trump Tariff Policy in 2025 - Ibnu Naufal Fuad Nurudin Fadhillah; Imam Tantowi; Acep Rahmat; Saepulloh Saepulloh; Alfan Rohibani (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the phenomenon of the reciprocal tariff policy, also known as the Trump Tariff, enacted by the United States in 2025, and the response of Islamic capital market participants to this global event, observed through stock price volatility in the Jakarta Islamic Index (JII). A descriptive quantitative approach was employed to explain the results by presenting the collected data as they are, without attempting to draw generalizable conclusions. The data analysis methods used include the calculation of daily logarithmic returns, estimation of historical volatility using a 7-day rolling standard deviation, identification of tariff policy announcement dates in 2025, and visual interpretation of volatility pattern changes around that period in the observed market conditions. The results indicate that the Indonesian Islamic stock market (JII) experienced significant price fluctuations during the period of the new tariff policy under President Trump. Daily returns showed a negative tendency with an asymmetric distribution, reflecting market uncertainty in responding to global dynamics. The highest level of volatility occurred in April 2025, suggesting that the market reacted to global economic issues through increased price instability. This study demonstrates that external conditions such as tariff policies can influence market psychology and stability, even if not proven causally.